1989
DOI: 10.1212/wnl.39.2.235
|View full text |Cite
|
Sign up to set email alerts
|

Autopsy findings in a patient who had an adrenal‐to‐brain transplant for Parkinson's disease

Abstract: Autopsy findings in a patient who had an adrenal-to-brain transplant for Parkinson's disease 4 months before his death showed adrenal tissue in the basal ganglia, but it was necrotic. Symptomatic improvement lasted for only 2 weeks.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
19
0
1

Year Published

1989
1989
2011
2011

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 139 publications
(21 citation statements)
references
References 0 publications
1
19
0
1
Order By: Relevance
“…We propose that the poor survival of grafted chromaffin cells previously observed by our group Bing et al, 1990;Kordower et al, 1990a,b, 199 1) and others (Herrera-Marschitz et al, 1984;Morihisa et al, 1984;Stromberg et al, 1984;Freed et al, 1986;Bankiewicz et al, 1988;Frank et al, 1988;Hurtig et al, 1989;Jankovick et al, 1989;Peterson et al, 1989;Hirsch et al, 1990;Waters et al, 1990) is not due to the lack of NGF-mediated trophic support as previously believed. Rather, the fibroblasts and/or endothelial cells within the adrenal medulla appear deleterious to the viability of adrenal medullary grafts, an effect that can be overcome by NGF administration (Stromberg et al, 1985) or cografting with growth factor-producing cells Date et al, 1990a,b;Kordower et al, 1990a,b;Cunningham et al, 1991;Doering, 199 1;Chalmers et al, 1992).…”
Section: Discussionsupporting
confidence: 59%
See 2 more Smart Citations
“…We propose that the poor survival of grafted chromaffin cells previously observed by our group Bing et al, 1990;Kordower et al, 1990a,b, 199 1) and others (Herrera-Marschitz et al, 1984;Morihisa et al, 1984;Stromberg et al, 1984;Freed et al, 1986;Bankiewicz et al, 1988;Frank et al, 1988;Hurtig et al, 1989;Jankovick et al, 1989;Peterson et al, 1989;Hirsch et al, 1990;Waters et al, 1990) is not due to the lack of NGF-mediated trophic support as previously believed. Rather, the fibroblasts and/or endothelial cells within the adrenal medulla appear deleterious to the viability of adrenal medullary grafts, an effect that can be overcome by NGF administration (Stromberg et al, 1985) or cografting with growth factor-producing cells Date et al, 1990a,b;Kordower et al, 1990a,b;Cunningham et al, 1991;Doering, 199 1;Chalmers et al, 1992).…”
Section: Discussionsupporting
confidence: 59%
“…Some studies failed to demonstrate the survival of histochemically identified grafted chromaffin cells for more than 400 min (Herrera-Marschitz et al, 1984;StrGmberg et al, 1984), and macrophages and inflammatory cells appear to be the principal cell types within the graft region. Recent postmortem analyses of patients receiving chromaffin cell implants confirmed findings reported in nonhumans (Frank et al, 1988;Hurtig et al, 1989;Jankovick et al, 1989;Peterson et al, 1989;Hirsch et al, 1990;Waters et al, 1990), with only one study demonstrating the survival of a few tyrosine hydroxylase (TH)-immunoreactive cells (Kordower et al,199 1).…”
mentioning
confidence: 79%
See 1 more Smart Citation
“…Survival of chromaffin cells transplanted into the brain parenchyma is, however, generally poor (Freed et al, 1986;Bohn et al, 1987;Hansen et al, 1988;Hurtig et al, 1989;Jankovic et al, 1989;Peterson et al, 1989;Hirsch et al, 1990;Kordower et al, 199 1). To increase the survival of grafted chromaffin cells, supplementation with NGF has been successfully employed (Stromberg et al, 1985;Date et al, 1990;Kordower et al, 1990;Cunningham et al, 1991).…”
mentioning
confidence: 99%
“…In spite of the political controversy involving this pioneer studies, the clinical improvement obtained in some patients set off the interest of transplant therapy in PD patients around the world (Deacon et al, 1997;Freed 1990Freed , 2001Hirsch et al, 1990;Itakura et al, 1997;Kordower 1995Kordower , 1996Lindvall et al, 1990;Peterson et al, 1989;Sawle et al, 1992;Watts et al, 2003) (See table 2). However, the employment of human fetal dopaminergic neurons as a DA source for transplant is a complicated approach, due to its availability, which is imposed by ethical affairs; for this reason, they have been only employed in some human cases (Freed et al, 1990;Hauser et al, 1999;Kordower et al, 1995;Lindvall, et al, 1990;Madrazo et al, 1988;Mendez et al, 2008;Sawle et al, 1992).…”
Section: Transplant Therapy In Pd Patients: a Leap Forward To A Potenmentioning
confidence: 99%